Live birth after in vitro maturation versus standard in vitro fertilisation for women with polycystic ovary syndrome: protocol for a non-inferiority randomised clinical trial - Jie Qiao; Rui Wang; Ben W Mol; Rong Li; Xiaoying Zheng; Lin Zeng; Lina Wang; Danni Zheng; Wei Guo; Shuo Yang (BMJ Open)
Introduction Polycystic ovary syndrome (PCOS) is the first common cause of anovulatory infertility. Currently, in vitro fertilisation (IVF) is recommended when conventional attempts have failed. In vitro maturation (IVM) of human oocytes is an emerging treatment option in infertile women with PCOS. It is a patient-friendly intervention, avoiding the risk of ovarian hyperstimulation syndrome, which is a serious complication of controlled ovarian stimulation in the standard IVF procedure. We plan a randomised controlled trial (RCT) to evaluate whether IVM is non-inferior to the standard IVF for live birth in women with PCOS.Methods and analysis This is a single-centre, open-label, non-inferiority RCT performed in a large reproductive medicine centre in China. Infertile women with PCOS will be randomised to receive either IVM or standard IVF in a 1:1 treatment ratio after informed consent. IVF procedures used in our study are all standard treatments and other standard-assisted reproductive technologies will be similar between the two groups. The primary outcome is ongoing pregnancy leading to live birth within 6 months of the first oocyte retrieval cycle after randomisation. Pregnancy outcome, maternal safety and obstetric and perinatal complications will be secondary outcomes. The planned sample size is 350 (175 per group).Ethics and dissemination Ethical permission was acquired from the Ethics Committee of Peking University Third Hospital. The results will be issued to publications through scientific journals and conference reports.Trial registration number NCT03463772.